Topics in Sports Finance - Barajas, Angel (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Sports economics is a relatively new field of research that is experiencing rapid growth in the economics literature. The importance of the sports industry to economies coupled with the availability of financial and productivity data have made the study of sports economics a useful avenue for exploring research questions that have eluded mainstream economics fields. The main goal of this Special Issue of the International Journal of Financial Studies is to encourage theoretical and applied research in sports economics, which is of interest to both academics and practitioners. For this purpose, this Special Issue on "Sports Finance" invites papers on topics, such as, but not limited to, salary determination, ticket pricing, revenue sharing, salary caps, competitive balance, new stadium financing, rival league behavior, determinants of revenue, television and media, tournament prize structures, financial distress in professional sports, financial fair play, financial control of sports clubs, Third Party Ownership, financial efficiency in professional sports, budget constrains and sport performance, financial information of sports, ownership of professional sport clubs and Crowdfunding in sports. Papers on both professional and amateur sports are welcome.